2017
DOI: 10.2196/publichealth.6492
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Depressive Symptoms and Nonresponsive Feeding Styles and Practices in Mothers of Young Children: A Systematic Review

Abstract: BackgroundChildhood obesity is a significant global public health problem due to increasing rates worldwide. Growing evidence suggests that nonresponsive parental feeding styles and practices are important influences on children’s eating behaviors and weight status, especially during early childhood. Therefore, understanding parental factors that may influence nonresponsive parental feeding styles and practices is significant for the development of interventions to prevent childhood obesity.ObjectiveThe object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 79 publications
(262 reference statements)
2
13
0
Order By: Relevance
“…The relationship between maternal psychopathology and maternal feeding styles and practices have previously been assessed in several studies [62,63,[68][69][70] and systematic reviews [71,72]. Our results are in concordance with this research, suggesting that maternal mental health issues may interfere with the ability to promote a healthier feeding environment with positive social interactions.…”
Section: Plos Onesupporting
confidence: 89%
“…The relationship between maternal psychopathology and maternal feeding styles and practices have previously been assessed in several studies [62,63,[68][69][70] and systematic reviews [71,72]. Our results are in concordance with this research, suggesting that maternal mental health issues may interfere with the ability to promote a healthier feeding environment with positive social interactions.…”
Section: Plos Onesupporting
confidence: 89%
“…Several studies have noted that depressed mothers tend to feed their children in a less responsive fashion compared with mothers with normal mood (Goulding et al, 2014;Gross et al, 2013;Haycraft, Farrow, & Blissett, 2013;McCurdy, Gorman, Kisler, & Metallinos-Katsaras, 2014;Mitchell, Brennan, Hayes, & Miles, 2009). In a systematic review (Lindsay et al, 2017), two of three studies reported mothers with increased depressive symptoms were less likely to feed their children in a responsive manner. A nonresponsive feeding style may take several forms, being either forceful (strictly controlling the child's intake), indulgent (acquiescing to the child's wishes with little parental guidance), or uninvolved (allowing the child significant autonomy in making eating decisions; Hurley, Black, Papas, & Caufield, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding style, the manner in which mothers interact with children in feeding situations, is one of the most plausible candidates for linking maternal depression, diet quality, and children's weight (Lindsay, Mesa, Greaney, Wallington, & Wright, ). As with parenting style, feeding style is often described in terms of the underlying dimensions of demandingness and responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Parent feeding behaviors have important implications for children's health outcomes, such as weight and the ability to self-regulate eating (Faith et al, 2004;Frankel et al, 2012). "Nonresponsive feeding behaviors" are characterized by parents failing to observe cues or listen to their children's feedback about hunger or fullness during feeding (Lindsay et al, 2017). Distrust in children's appetite, rewards around food, and pressure to eat all fall under the umbrella of nonresponsive feeding behaviors (Jansen et al, 2014).…”
mentioning
confidence: 99%